ASPECTS: LINGUISTICS APPROACH IN EXPLAINING ENGLISH TO INDONESIAN LEARNERS - Nofel Nafiadri (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Bahasa Indanesia, one of Malay varieties, has no tenses marker. Meamuhile, English v,hich is taught at schools anduniversities in Indonesia has complicated-full of exceptions- tenses marker. The diversity of both languages in grammatical system, such as tenses, becomes a priority and a point of attention in teaching and learning English in Indonesia. Students are familiar with tenses names and sentence formulas but mostly encounter problems in the use of them. The absent of tenses marking system in Bahasa Indonesia is considered as the main reason for students' failure of doing analogy. Most teachers have introduced that English has sixteen or twelve tenses. Rules and exceptions of the agreement sysletn in English come into a complicated thing for the learners such as third singular subjects in present tense. Linguistics and Typological approach between Indonesian and English language in teaching English grammar should come to a consideration. Therefore, rather than explaining English has twelve tenses without comparing to lndonesian grammatical system, this article puts forward the introduction of aspects in explaining English tenses. By reintroducing that English has only two tenses which are present and past tense, while the continuous and perfect are aspects in English, teachers and students could do simplifcation in understanding contplicated English tenses.